1991
DOI: 10.1159/000247627
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment in Stage I and II Malignant Melanoma: A Randomized Trial between Chemoimmunotherapy and Immunotherapy

Abstract: A randomized trial comparing chemoimmunotherapy (bacillus Calmette-Guérin + chemotherapy) and immunotherapy (bacillus Calmette-Guérin alone) was carried out in high-risk stage I and II malignant melanoma patients. Eighty-two evaluable patients were included. The follow-up median duration was 11 years. Recurrent melanoma developed in 28 patients (34%). The overall survival rate was 76% at 5 years and 65% at 10 years. There were no statistical differences in survival probability or disease-free survival (DFS) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Multiagent cytotoxic therapy is similarly unhelpful in the adjuvant setting. Other trials of multiagent chemotherapy using nitrosoureas, dactinomycin and vincristine present contrary results (1983, Castel et al, 1991, McClay et al, 2000, Pawlik and Sondak, 2003, Wood et al, 1978).…”
Section: Adjuvant Therapymentioning
confidence: 96%
“…Multiagent cytotoxic therapy is similarly unhelpful in the adjuvant setting. Other trials of multiagent chemotherapy using nitrosoureas, dactinomycin and vincristine present contrary results (1983, Castel et al, 1991, McClay et al, 2000, Pawlik and Sondak, 2003, Wood et al, 1978).…”
Section: Adjuvant Therapymentioning
confidence: 96%
“…A trial using BCNU, dactinomycin, and vincristine [58] and a small trial of DTIC, CCNU, and vincristine [59] both suggested a benefit for multiagent chemotherapy, while two other trials did not [60,61]. Several small trials have also explored postoperative adjuvant therapy with DTIC plus BCG, with [55,62] or without a no-treatment arm [63][64][65][66][67]. DTIC plus BCG does not appear to have any efficacy in the adjuvant setting, which is hardly surprising in view of the lack of activity of the individual agents and the absence of any suggestion of synergy between them.…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…Early trials utilized low-or intermediate-dose regimens, and while there was a suggestion of some effectiveness [92,93], re-analysis and additional trials have demonstrated no benefit to survival [94,95]. Although there was no overall survival advantage, the disease-free survival advantage to low-dose IFN seen in the French and Austrian trials has led to its approval in Europe for thick primary melanomas [66,67] Unfortunately, the recently published results of the AIM-HIGH study in the United Kingdom of low-dose extendedduration IFN-α2a demonstrated no clear differences between IFN and observation in either overall or relapsefree survival for any subset of patients [98].…”
Section: High Dose Interferon-α2bmentioning
confidence: 99%